ROLE OF CORONARY COMPUTED TOMOGRAPHY ANGIOGRAPHY IN DIAGNOSIS OF STABLE CHEST PAIN (Journal of Academic Research, 2023)
Chest pain is often the herald of cardiovascular disease and is one of the most common diagnostic challenges encountered by practicing clinicians. Cardiovascular disease remains a leading cause of morbidity and mortality worldwide, despite advances in medical and procedural therapies.     Coronary Cardiac computed tomography angiography is a radiographic test that allows visualization the presence and severity of coronary artery stenosis. It is an anatomical test that can be used in patients with stable chest pain.     This study aims to find the role of CCTA in diagnosis of non acute chest pain. So 40 case study of patient complaining of non acute chest pain were conducted in Tripoli University Hospital by primary investigation and evaluated by Coronary computed tomography angiography technique (CCTA).